Effect of supplementary cementitious materials on shrinkage and crack development in concrete - Akkaya, Yilmaz; Ouyang, Chengsheng; Shah, Surendra P. (Elsevier BV, 2007)
The autogenous and drying shrinkage of Portland cement concrete, and binary and ternary binder concretes, were measured and compared. The binary and ternary binder concretes were formed by replacing part of the cement with fly ash, very fine fly ash and/or silica fume. Restrained shrinkage test was also performed to evaluate the effect of binder type on early age cracking. After the cracking of the restrained ring samples, crack widths were measured and compared with the results of an R-curve based model, which takes post-peak elastic and creep strains into account. The incorporation of fly ash and very fine fly ash decreased the autogenous shrinkage strain but increased the drying shrinkage strain. Since the total shrinkage strains of both the ternary and the binary concrete mixtures were similar, the strength development became an important factor in the cracking. The lower strength of the concrete with ternary binders led to earlier cracking compared to the binary binder concrete. Portland cement concrete cracked the earliest and had the greatest crack width. Measured crack widths were in accordance with the crack widths calculated with the R-curve model.